The Effect of Different Bases of Vegetable and Carrageenan Concentrations on The Quality of The Mix Vegetable Leather of Lettuce and Mustars Greens - Sabila, Cut Putri Hadiati; Mujdalipah, Siti; Fishi, Ana Nadiya Afinatul (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2024)
The benefits of each vegetable are different, one vegetable cannot be substituted for another. Vegetable processing in Indonesia is still very limited to sautéed, boiled, steamed or eaten directly, meaning that people's interest in vegetable consumption is still relatively low. However, increasing public awareness of the use of vegetables encourages variations in vegetable processing. One of the processing that can be applied to vegetables is manufacturing mix vegetable leather. Vegetable leather is a processed product derived from crushed and dried vegetables. The diverse benefits of each vegetable encourage its creationmix vegetable leather orvegetable leather which uses more than 1 vegetable as the basic ingredient. Mustard greens and lettuce are vegetables with high production in Indonesia. Apart from that, the crude fiber from mustard greens is 51.07%, while lettuce contains 50.7% crude fiber. The purpose of this study is to obtain the effect of vegetable basis and carrageenan concentration variance on mix vegetable leather of lettuce and mustard greens. The increase of people awareness of vegetable utilization drives to variate the vegetable processing. Each vegetable has its own unique benefits thus they could not be easily subtituted and mixed. This study used RAL with two factors, those are variety of vegetable basis between lettuce and mustard greens (30,50,100) and carrageenan consentration (1% and 1,5%). The chemical respond in this study covers moisture content, ash content, and crude fiber, while the organoleptic respond covers color, aroma, flavor, and texture. The best treatment is found on A1B1, that has 30 g for vegetable basis and 1% of carrageenan consentration with 13,31 % moisture content, 12,29% ash content, 8,24% crude fiber, 3,7 score in color and 2,05 color quality; aroma 3.23 and aroma quality 2.80; taste 3.40 and taste quality 3.06; and texture 3.46 and texture quality 3.73.